Black Carbon Emission Reduction Due to COVID‐19 Lockdown in China. Issue 8 (21st April 2021) - Jia, Mengwei; Evangeliou, Nikolaos; Eckhardt, Sabine; Huang, Xin; Gao, Jian; Ding, Aijun; Stohl, Andreas
Abstract: During the Lunar New Year Holiday of 2020, China implemented an unprecedented lockdown to fight the COVID‐19 outbreak, which strongly affected the anthropogenic emissions. We utilized elemental carbon observations (equivalent to black carbon, BC) from 42 sites and performed inverse modeling to determine the impact of the lockdown on the weekly BC emissions and quantify the effect of the stagnant conditions on BC observations in densely populated eastern and northern China. BC emissions declined 70% (eastern China) and 48% (northern China) compared to the first half of January. In northern China, under the stagnant conditions of the first week of the lockdown, the observed BC concentrations rose unexpectedly (29%) even though the BC emissions fell. The emissions declined substantially thereafter until a week after the lockdown ended. On the contrary, in eastern China, BC emissions dropped sharply in the first week and recovered synchronously with the end of the lockdown. Plain Language Summary: During the lockdown that was implemented to fight the COVID‐19 disease in China, most traffic and production activities were suddenly interrupted, resulting in unprecedented abrupt anthropogenic emission changes. We performed inverse modeling based on black carbon observations to reveal the regional changes of BC emissions in densely populated eastern and northern China on a weekly basis from January 1 to March 10, 2020. We found maximum reductions of 70% in eastern China and 48% in northern China and also found different storylines of the emission responses to the lockdown in these two regions. With the high spatio‐temporal resolution emissions and the understanding of the meteorological processes, the abnormal BC observations of the first week of the lockdown were quantified. This study provides not only emission information deriving from the impacts of the disastrous pandemic, but also a competitive method to assess the influences of meteorological conditions on air pollutants. Key Points: Inverse modeling based on measurements at 42 sites was conducted to investigate the black carbon (BC) emission changes during the COVID‐19 in China With 70% and 48% BC emission reductions, large regional and temporal differences existed in eastern and northern China during the lockdown By inverse modeling, the effect of stagnant conditions on ambient BC concentrations can be quantified